The Latest Development of Chile-Bolivia Dispute: Questioning International Watercourse Status of Silala/Siloli in ICJ - Almi Nibach Mauludila (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Silala/Siloli is a basin, an international watercourse, flow from highlands of Potosí, Bolivia, to Antofagasta, Chile. Since 1997, Bolivia claims full sovereignty over the watercourse based on the canalisation of Silala/Siloli in 1908. On the other hand, Bolivia has never argued on the existence and status of Silala/Siloli for over 90 years before. Until now, Chile uses the flow to water the cities of Antofagasta, Sierra Gorda, and Baquedano. Recently, the situation is worsened by Bolivia’s decision to conduct several projects around Silala/Siloli. Chile filed its objection to the ICJ on June 2016. In 2018, both parties have concluded the written proceeding by submitting their memorials. The oral proceeding for this contentious case is yet to be decided. This study aims to analyze the definition of international watercourse based on international law. The analysis started from the ILC Guiding Principles on Unilateral Declaration capable of creating legal obligations, general principles regarding territorial claim, and relevant bilateral documents between the two States.Perkembangan Terakhir Chile v. Bolivia di Mahkamah Internasional: Sengketa Status Silala/Siloli sebagai Jalur Air InternasionalAbstrakSilala/Siloli adalah jalur air internasional yang berasal dari dataran tinggi Potosí, Bolivia dan mengalir ke Antofagasta, Chili. Pada tahun 1997, Bolivia mengklaim kedaulatan penuh atas aliran air Silala/Siloli dengan mendasarkan argumen pada kanalisasi di tahun 1908. Di sisi lain, keberadaan dan status Silala/Siloli tidak pernah diperdebatkan oleh Bolivia selama lebih dari 90 tahun. Hingga saat ini, Chili menggunakan Silala/Siloli untuk mengairi kota Antofagasta, Sierra Gorda, dan Baquedano. Baru-baru ini, situasinya diperburuk oleh keputusan Bolivia untuk melakukan beberapa proyek di sekitar Silala/Siloli. Chili mengajukan klaimnya ke ICJ pada Juni 2016 dan pada 2018 kedua belah pihak telah menyelesaikan tahap tertulis dengan mengirimkan memorial. Proses persidangan ini belum ditentukan. Artikel ini akan menganalisis definisi jalur air internasional menurut hukum internasional. Analisis akan dimulai pada Prinsip-Prinsip Panduan ILC tentang Deklarasi Unilateral yang mampu menciptakan kewajiban hukum, prinsip-prinsip umum mengenai klaim teritorial, dan dokumen bilateral yang relevan antara kedua Negara.DOI: https://doi.org/10.22304/pjih.v5n3.a2